THE IMPACT OF CYBERBULLYING ON ADOLESCENT MENTAL HEALTH: A PANCASILA-BASED APPROACH AS A SOLUTION - Fadila Syahda, Qori; Sitorus, Michael (SIWAYANG Journal: Publikasi Ilmiah Bidang Pariwisata, Kebudayaan, dan Antropologi, 2024)
The rapid advancement of information technology has significantly impacted various aspects of human life, particularly in the realm of social media usage. While social media platforms offer numerous benefits, they also present substantial negative implications, one of the most alarming being the rise of cyberbullying. This behavior often originates from repeated negative comments that can severely affect the mental health of victims. Therefore, fostering ethics in digital communication is imperative. This study aims to examine the ramifications of cyberbullying and explore how values rooted in Pancasila can be integrated into society as a countermeasure. Utilizing a qualitative research method with a literature review approach, this investigation delves into the increasing prevalence of cyberbullying among adolescents. Furthermore, it discusses viable solutions to ensure the preservation of Pancasila values amidst technological advancements. The findings illustrate that embedding Pancasila values into daily life significantly shapes more responsible community behavior. By adhering to the moral guidelines provided by Pancasila, individuals are equipped to act with greater wisdom and empathy, consequently fostering a more harmonious social environment and promoting positive online interactions.